An ivory statuette depicting the god Thanatos discovered near Tomis (Moesia Inferior) - Ingrid Petcu-Levei; Radu Petcu (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
In recent years, real estate developments in Constanța prompted a series of preventive archaeological investigations, leading to the discovery of rich archaeological material. These finds include a bone statuette found in the Palazu Mare district of Constanța. In this context, the nucleus of habitation, previously inferred from various archaeological finds from the Roman period, has been identified. Numerous surveys and preventive archaeological investigations have allowed for a clearer delimitation of the archaeological site of Palazu Mare. Regarding chronology, the settlement (possibly a vicus) can be dated from the 2nd–3rd centuries to the early decades of the 4th century AD. The statuette in question was carved out of ivory, measuring 6 cm in height and 1.7 cm in width. It was made as a representation of the god Thanatos, the personification of the Angel of Death in Greek and Roman mythology. Unfortunately, the statuette is incomplete; the left hand and parts of the legs are missing, along with the wings originally located on its back. The closest analogy for our representation comes from Northern France, where a small bronze statue was discovered in a villa rustica in Salouël, a commune located on the outskirts of Amiens. Due to the uncertainty surrounding the function of the object to which the statue pertains, we classify it as instrumentum domesticum, a category that includes a variety of objects that were part of everyday Roman life. The discoveries made here are considered quite rare due to the material of the statuette, and the context in which it was found. Based on previous observations, it can be said that Thanatos is typically a characteristic of funerary art and is therefore rarely found in domestic contexts. Ivory statues are particularly uncommon in the Dobrudja region of Moesia Inferior.